Oregano-based feed additive reduces Salmonella enterica serovar Enteritidis colonization in young broilers - Christina L. Swaggerty; M. Dolores Cabrera; Santiago Sasia; Gabriel Cabrera; Kenneth J. Genovese; J. Allen Byrd, II; Michael H. Kogut; Rafael A. Cabrera (Poultry Science, 2025)
Salmonella is one of the leading bacterial foodborne pathogens and is commonly found in poultry. The objective of this study was to determine if feeding an oregano-based antibiotic alternative could reduce the burden of Salmonella in broilers. Day-of-hatch straight-run broiler chicks were provided a basal corn-soymeal diet. After four days on the basal diet, birds were assigned to a dietary treatment group (n = 50 chicks/group/experiment). The groups were control with no oregano feed additive or a diet supplemented with an oregano oil product (300 g/ton). At 7-days-of-age, chicks were challenged via oral gavage (0.5 mL) with Salmonella enterica serovar Enteritidis (1 × 104-5 colony forming units [cfu]/chick). Fourteen-days post-challenge (dpc), 50 birds from each group were euthanized. At necropsy, the liver and one cecal pouch were removed and enriched for S. Enteritidis and cecal content was analyzed for S. Enteritidis enumeration. The study was conducted twice. Data were analyzed to determine differences in S. Enteritidis recovered between the groups with P < 0.05 significant. No differences were observed in the percent positive liver samples in the controls compared to those on the oregano diet. There was a reduction (P = 0.003) in the positive ceca between controls (61 %) compared to chickens on the oregano diet (40 %). The S. Enteritidis recovered from cecal content was also reduced (P < 0.001) in chickens on the oregano diet (3.2 × 103 cfu/g) compared to controls (3.5 × 105 cfu/g). Cytokine (IL-1β, IL-18) and chemokine (CXCL8) mRNA expression was also 1.9-2.2-fold higher (P ≤ 0.04) in the cecal tonsil of chickens on the oregano diet compared to controls indicating immunomodulatory affect. Collectively, these data demonstrate addition of an oregano-based feed additive to a broiler diet reduces S. Enteritidis colonization and invasion in the ceca and may be an important pre-harvest intervention strategy to reduce the burden of this highly important foodborne pathogen.